2019
DOI: 10.1038/s41375-019-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of the E3 ubiquitin ligase SKP2 in T-ALL

Abstract: Timed degradation of the cyclin-dependent kinase inhibitor p27 Kip1 by the E3 ubiquitin ligase F-box protein SKP2 is critical for T-cell progression into cell cycle, coordinating proliferation and differentiation processes. SKP2 expression is regulated by mitogenic stimuli and by Notch signaling, a key pathway in T-cell development and in T-cell acute lymphoblastic leukemia (T-ALL); however, it is not known whether SKP2 plays a role in the development of TALL. Here, we determined that SKP2 function is relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…IL-7, produced in the bone marrow and thymus, is a major microenvironmental signal promoting T-ALL cell expansion [26,39,[42][43][44]48,[55][56][57]. We have previously found that CK2 activity is mandatory for optimal IL-7/IL-7R-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…IL-7, produced in the bone marrow and thymus, is a major microenvironmental signal promoting T-ALL cell expansion [26,39,[42][43][44]48,[55][56][57]. We have previously found that CK2 activity is mandatory for optimal IL-7/IL-7R-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that SKP2 and FBXL12 are both required for T cell development in an identical and additive manner as result of their targeting the same protein. Consideration of the potential of inhibition of the SKP2-p27 KIP1 pathway for the treatment of T cell leukemia [252] should thus take into account the role of FBXL12.…”
Section: P27 Kip1mentioning
confidence: 99%
“…Standard retrovirus infections were performed as previously report with slight modifications ( Kobayashi et al, 2017 ; Rodriguez et al, 2020 ). YS or P-Sp derived hematopoietic cells, 6–7 days after co-culture with OP9-DL1, were plated at 2.5 × 10 5 cells per well on a 24 well plate the day before viral transduction.…”
Section: Methodsmentioning
confidence: 99%